1999
DOI: 10.1103/physrevb.60.11963
|View full text |Cite
|
Sign up to set email alerts
|

Different crystal chemistries of the117Cd117

Abstract: The nuclear-electric-quadrupole interactions at 117 In and 111 Cd nuclei arising from 117 Cd and 111m Cd, respectively, each chemically introduced in ferroelectric LiNbO 3 (T C ϭ1483 K) and LiTaO 3 (T C ϭ938 K) polycrystals, were studied by measuring the time-differential perturbed angular correlation of ␥ rays over a temperature range from 4.2 to 1243 K. Well-defined, essentially single, static electric quadrupole frequencies were observed for 117 In and 111 Cd in the oxides. It has been established that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…We performed PAC measurements on 117 In ͑arising from 117 Cd via nuclear decay͒ in polycrystalline samples of 8-mol % In-doped LT in a temperature range covering T C of 818 K. In addition, we performed PAC measurements on 111 Cd (← 111m Cd). Although Cd also occupies the Li site, as was confirmed in our previous PAC measurements for LN and LT, 7 the order-disorder transition of Cd can be different from that of In. Owing to the much larger ionic size 8 of Cd 2ϩ ͑95 pm͒ than that of Li ϩ and In 3ϩ , Cd may not even be dynamically disordered.…”
Section: Safaryansupporting
confidence: 73%
“…We performed PAC measurements on 117 In ͑arising from 117 Cd via nuclear decay͒ in polycrystalline samples of 8-mol % In-doped LT in a temperature range covering T C of 818 K. In addition, we performed PAC measurements on 111 Cd (← 111m Cd). Although Cd also occupies the Li site, as was confirmed in our previous PAC measurements for LN and LT, 7 the order-disorder transition of Cd can be different from that of In. Owing to the much larger ionic size 8 of Cd 2ϩ ͑95 pm͒ than that of Li ϩ and In 3ϩ , Cd may not even be dynamically disordered.…”
Section: Safaryansupporting
confidence: 73%
“…In a previous work, 11) we confirmed that an order of 1 mol% of Cd occupy the Li sites of LiNbO 3 and LiTaO 3 . We now examine whether an order of 10 mol% of Cd occupy the Li sites and thus a compound with the chemical formula Li 0.833 Cd 0.083 TaO 3 was actually prepared.…”
Section: Discussionsupporting
confidence: 63%
“…9)) can be explained as follows. Since the charge on an In ion at the Li site of LiTaO 3 is considered to be close to 3+, 11) and its ionic size (80 pm) is about the same as that of Li + (76 pm), 4) the In ion must come closer to the upper oxygen triangle than does a Li ion, because of its stronger Coulomb interaction with oxygen ions. This makes the inner space of the triangle more open, and thus a single In ion doped in LiTaO 3 as an impurity becomes disordered at a much lower temperature than Li would require.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAC measurement system used in this study is the same that was mentioned in [9]. The directional anisotropy A 22 G 22 (t) derived from the measurement, denoted as R(t) in Figure 2, is expressed as follows for an ensemble of randomly oriented molecules in liquid but in inactive molecular motion.…”
Section: Methodsmentioning
confidence: 99%